The experiences of 'significant others' supporting people with severe burn injury: An integrative literature review. Issue 3 (May 2022) - Flannery, Elizabeth; Halcomb, Elizabeth; Peters, Kath; Murphy, Gillian; Ramjan, Lucie M.
Abstract: Background: Severe burn injury is a traumatic experience for both patients and their significant others. Although research has focused on the experience of people with burn injury, there is a paucity of research focusing on the experiences of the significant other. Significant others are frequently expected to advocate and make decisions on behalf of the patient, which may have an impact on their psychological wellbeing. An understanding of the experiences of significant others will inform strategies to better support their needs. Objectives: The aim of this integrative literature review was to critically examine research related to the experiences of significant others supporting a patient with a severe burn injury in the hospital. Methods: CINAHL Plus with Full Text (EBSCO), MEDLINE ALL (Ovid), Scopus, and APA PsycINFO were searched up to December 2019 for English language studies using search terms burns, significant other, ICU, and psychological impact. Records were independently screened and assessed for methodological quality, and the data were synthesised. Results: Nine articles were included in the review. Three used a quantitative approach, and six were qualitative studies. Three major themes were identified, namely, (i) psychological consequences and emotional trauma, (ii) redefining relationships, and (iii) coping strategies. Conclusion: The review identified that significant others experience adverse psychological consequences including post-traumatic stress, anxiety, and depression. The burn injury resulted in a redefining of relationships with others and particularly with the patient through this shared experience. Significant others found ways to adapt to stressors, including taking control of the situation and seeking greater involvement in the patient's care.